The Effect of Pancasila Education Learning in Shaping Digital Literacy of Young Citizens (A Descriptive Study on 10th Grade Students in High Schools in Banyumas Regency) - Safriana Salsabilla; Eko Priyanto; Wildan Nurul Fajar (UM Purwokerto Press, 2023)
This research aims to determine the effect of Pancasila education learning in shaping digital literacy among young citizens, specifically 10th-grade students in high schools in Banyumas Regency. The method used in this research is descriptive research with a quantitative approach. The population for this study consists of 10th-gradestudents from SMA 1 Ajibarang, SMA 2 Purwokerto, SMA IT Al Irsyad Al Islamiyyah Purwokerto, and SMA Muhammadiyah Boarding School Ajibarang. The sample size is 99 students, determined through quota sampling.Data collection techniques used in this research include questionnaires, interviews, and documentation. The data analysis technique used is descriptive data analysis. This research indicates a positive and significant effect ofPancasila education learning in shaping digital literacy among young citizens, specifically 10th-grade students inhigh schools in the Banyumas Regency. The influence of the Pancasila education learning variable in shaping digital literacy among young citizens, specifically 10th-grade students in high schools in Banyumas Regency, is 0.234. This can be interpreted as Pancasila education learning contributes approximately 23.4% to digital literacy,while the remaining 76.6% is influenced by other factors not examined in this research.